Influence of crank length on pedalling economy in the acceleration phase in trackcycling - A single case study - Kuhlmann, C. H.; Jaitner, T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to identify different effects of crank-length on cycling performance in track cycling. Two different crank lengths (162,5mm and 170mm) were used in a single-blind and balanced order at a wooden indoor cycling track. Saddle height and the position of the handlebar were kept constant during all trials. The subject was asked to complete 100m with maximum load with every crank length in each test session. To avoid test effects and effects from fatigue, the order of crank length was changed throughout all test sessions. Measured variables were torque (Nm), power output (W), Force (F), Cadence (rpm) and time (s). Results showed that force output stayed constant, while the 170mm condition had advantages in time, torque and power output due to the longer lever arm. Longer distances than 100m were not analysed.